PARTICIPATORY PEER-GROUP MENTORING TO STRENGTHEN REPRODUCTIVE HEALTH AMONG SANTRI AT MADRASAH ULUMUL QUR’AN BUSTANUL ULUM, LANGSA - Nurhayati Nurhayati; Fitria Ulfah; Putra Apriadi Siregar; Nuraisyah Wulandari Panjaitan; Zahrani Nabilah; Faiza Adinda; Putri Safira (Journal of Gender and Social Inclusion in Muslim Societies, 2025)
Adolescent reproductive health is a critical public health issue, especially in conservative Islamic boarding schools (pesantren) where cultural and religious norms often restrict open discussion. Data from the WHO and the National Population and Family Planning Board (BKKBN) indicate high rates of unintended pregnancy and a significant knowledge gap among female students regarding menstruation, STIs, and self-protection. At Madrasah Ulumul Quran Bustanul Ulum Langsa, Aceh, the absence of an integrated reproductive health curriculum has resulted in inadequate student knowledge. This community service project aimed to enhance santri (students') understanding of reproductive health and empower them as peer educators to disseminate information, reduce stigma, and strengthen the pesantren's role. A key objective was to create safe spaces for dialogue and improve girls' communication skills on reproductive issues. The program employed the Asset-Based Community Development (ABCD) methodology, commencing with appreciative inquiry and asset mapping, followed by peer educator training, simulations, and pretest-posttest monitoring and evaluation. It involved 30 female santri selected via total sampling. Data were analyzed using a Dependent t-Test with JASP 16 software. The implemented strategy featured active engagement of students, caregivers, and educators, the development of digital and print educational media, and cross-sectoral collaboration. Santri were trained to convey materials in a contextual and culturally appropriate manner. Results indicated a highly significant improvement in attitudes (p < .001) post-intervention, while knowledge levels, already high at baseline, remained stable. The program's implications include fostering a more open pesantren environment for reproductive health education, strengthening santri capacity as change agents, and nurturing a generation that is health-conscious, responsible, and resilient.